Character Development Model for Kindergarten Students Based on the Pancasila Student Profile Strengthening Project (P5) in Mataram, Indonesia - Yumna Arifamahira; Windy Rahmania Octaviani; Afina Rosmalia; Baiq Wike Pratamaswari; Bq. Ulan Saswari Aji; Lalu Sumardi (International Journal of Education and Digital Learning (IJEDL), 2024)
The importance of character education in early childhood cannot be ignored because this phase is the "Golden Age" or golden period where the foundation of character and personality begins to form. For this reason, the Ministry of Education and Culture of the Republic of Indonesia issued the P5 program as an effort to strengthen character from an early age. This program requires all levels of education to implement P5, but in reality the implementation of the P5 program in kindergarten is still not optimally organized, so it does not have well-structured Planning, Management, Implementation, and Processing. On the other hand, Permata Hati Islamic Preschool Kindergarten has implemented the P5 Program consistently for a long time, so that this institution shows mature readiness in its implementation as an effort to strengthen the formation of positive character in early childhood. This study aims to analyze and identify the integrated P5 growth and development model. This study uses a qualitative approach, with data collected through observation, interviews, and documentation. The results of the study show that strengthening children's character in Permata Hati Islamic Preschool Kindergarten through the P5 learning model has been carried out well, structured and systematically. The character strengthening that is focused on consists of having faith, piety and noble morals, strengthening cooperation and mutual assistance, instilling the values of responsibility and environmental concern, independence and discipline, creativity and innovative intelligence.